2020
DOI: 10.9734/ajaees/2019/v37i430288
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate Change on Cereal Yield and Production in the Sahel: Case of Burkina Faso

Abstract: Climate change is one of the biggest challenges of the 21st century. It affects all countries in the world, especially Sahelian countries in Africa. This paper aimed at evaluating the impact of climate change on cereal yield in Burkina Faso. The ordinary least squares (OLS) was applied to time-series data from 1991 to 2016 collected on the World Bank website. The results have shown that temperature adversely affects yield and cereal production, while precipitation has positive effect. An increase in rainfall o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 4 publications
9
13
0
Order By: Relevance
“…This results implies that 1% increase in the mean level of temperature will decrease wheat production by 0.29% and 0.38%. Our results related to temperature are consistent with the outcomes of previous research works of Pickson et al (2020) and Sossou et al (2019), who reported that temperature has negative impacts on cereal production. Further results reveal that precipitation has positive impact on wheat production in both cases.…”
Section: Long-and Short-run Estimates For Model (I)supporting
confidence: 93%
“…This results implies that 1% increase in the mean level of temperature will decrease wheat production by 0.29% and 0.38%. Our results related to temperature are consistent with the outcomes of previous research works of Pickson et al (2020) and Sossou et al (2019), who reported that temperature has negative impacts on cereal production. Further results reveal that precipitation has positive impact on wheat production in both cases.…”
Section: Long-and Short-run Estimates For Model (I)supporting
confidence: 93%
“…This indicates that cereal crop yields show a strong correlation with temperature change, and temperature will be a significant factor for northern Togo cereal crop yields in the future [18,48]. These results are in line with those of Sossou et al [50], who stated that temperature affects cereal yield in the long and short terms in Burkina Faso. In addition, the combined effect of rainfall and temperature on the cereal crop yields in all the four locations is significant with a positive or negative sign.…”
Section: Significance Of Temperature and Rainfall Variability For Cersupporting
confidence: 88%
“…It is evident from the results that there is an imperative need to adopt appropriate adaptation strategies to curb the negative effects of climate change on cereal production, as highlighted by Nyuor et al [44] in Ghana, Hounnou et al [53] who evaluated the effects of climate change on the agricultural sector in Benin, and Nana [54] who analysed the impact of climate change on cereal production in Burkina Faso. Similarly, Sossou et al [50] recommended implementing effective adaptation strategies in Burkina Faso as a conclusion to their study of the impact of climate change on cereal yield and production in that country. In this regard, many actions have been taken by the Ministries of Agriculture and the Environment, which implementations were facilitated by the fact that farmers in the study area are gradually receptive to new agricultural technologies such as climate-smart agriculture practices offered by agricultural extension officers [37].…”
Section: Significance Of Temperature and Rainfall Variability For Cermentioning
confidence: 99%
“…Recent decade droughts, floods and heats have severely impacted the country's farmer livelihoods, especially water resources Gahi et al, (2017). These different impacts of climate risks on hydrosystems have had adverse repercussions on livelihoods of communities that depend mainly on agriculture (Barbier and Yacouba, 2009;Zorom et al, 2013;Sossou et al, 2019). Gahi et al (2015) identified vulnerability factors for agricultural water, which significantly lead to decrease of crop production and food insecurity.…”
Section: Methodsmentioning
confidence: 99%
“…Filippi et al (1990) noted a continuous decrease in groundwater recharge in the Massili in Borogo and Silmissin, both in Burkina Faso; leading to a 1 to 1.9 m drop in the water table since 1980; and an average decrease in groundwater levels of 1 to 3 m nationally (Mouhouyouddine et al, 2017). Gahi et al (2019), they noted an early drying of community wells (up to 13 m in depth); while Sossou et al (2019) highlighted the impacts of climate drivers on crop yield. According to these authors, within a short term, an increase in temperatures of 1ºC would result in a decrease in cereal yield of 72 kg per hectare; while in the long-term period, a rise in temperatures of 1ºC would result in a decrease in cereal yield of 1074 kg per hectare.…”
Section: Introductionmentioning
confidence: 99%